OSCEai dermatology: augmenting dermatologic medical education with Large Language Model GPT-4 - Ye-Jean Park; Eddie Guo; Muskaan Sachdeva; Bryan Ma; Sara Mirali; Brian Rankin; Nikki Nathanielsz; Abrahim Abduelmula; Tatiana Lapa; Mehul Gupta; Trevor Champagne (Canadian Medical Education Journal)
Implication Statement